Sistem Informasi Penjualan Barang Kolportase Biro Zending HKBP Pematang Siantar Berbasis Web - Hutagaol, Ryan Philip; Saragih, Rijois I. E.; Perangin-angin, Resianta (Universitas Methodist Indonesia, 2024)
In this modern era, technological advances are developing rapidly, especially information technology. Information technology really helps people in getting information quickly and easily and makes work easier. Where activities include recording inventory of goods for inventory at the Zending HKBP colportage, making a list of purchases of goods, up to making sales reports and the problems that occur in carrying out inventory records of goods and making a list of purchases of goods is only done manually, while for making purchase and sales reports only relying on the existing application, namely Ms.Excel, but all of these recording processes often go wrong, require a long time and inaccurate data in making reports, so that reports are submitted late to the head of the HKBP Zending Bureau. So that in making a web requires collaboration between the above programs. This book ordering information system can make it easier for consumers or buyers to search books according to the category / type of book and make online purchases. With this web-based book ordering information website running on the internet network to make it easier for consumers without being limited by time, distance and weather.